Effects of Lactobacillus cultures on growth performance, abdominal fat deposition, serum lipids and weight of organs of broiler chickens - Kalavathy, R.; Abdullah, N.; Jalaludin, S.; Ho, Y.W. (Taylor and Francis Group, 2003)
The effects of a mixture of 12 Lactobacillus strains (LC) on the growth performance, abdominal fat deposition, serum lipids and weight of organs of broiler chickens were studied from 1 to 42 d of age. 2. One hundred and thirty-six 1-d-old male broiler chicks were assigned at random to two dietary treatments: a basal diet (control), and a basal diet with 0·1% LC. 3. The supplementation of LC in broiler diets improved the body weight gain and feed conversion rate from 1 to 42 d of age and was effective in reducing abdominal fat deposition but only after 28 d of age. 4. The LC diets reduced serum total cholesterol, low density lipoprotein (LDL) cholesterol and triglycerides in broilers from 21 to 42 d of age. However, there was no significant difference in serum high density lipoprotein (HDL) cholesterol between control and LC-fed broilers. There was also no significant difference in the weights of organs of control and LC-fed broilers. 5. The results indicated that the mixture of 12 Lactobacillus strains have a hypolipidaemic effect on broilers.